2007
DOI: 10.1093/humrep/dem313
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin B is superior to FSH as a serum marker for spermatogenesis in men treated for Hodgkin's lymphoma with chemotherapy during childhood

Abstract: The use of MOPP chemotherapy causes permanent gonadal damage in the far majority of male survivors of childhood Hodgkin's lymphoma and inhibin B is the most valuable serum marker for gonadal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…In addition, local radiotherapy to the testis was administered in five men who all showed extremely low Inhibin B levels. Although semen analyses were not available of these men, the previous published correlations between Inhibin B levels and sperm count indicates that these survivors probably have a severely impaired spermatogenesis [10,15].…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…In addition, local radiotherapy to the testis was administered in five men who all showed extremely low Inhibin B levels. Although semen analyses were not available of these men, the previous published correlations between Inhibin B levels and sperm count indicates that these survivors probably have a severely impaired spermatogenesis [10,15].…”
Section: Discussionmentioning
confidence: 94%
“…Although several studies have shown the value of modern fertility markers for prediction of spermatogenesis, studies on gonadal function after chemotherapy and irradiation in large series of adult male cancer survivors, using Inhibin B as a novel serum markers are lacking [5,15,[20][21][22]. Therefore, we performed a study in a full single center cohort of male childhood cancer survivors (n ¼ 248).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A central problem is the paucity of accurate information as to the degree of gonadotoxicity of chemotherapy regimens that develop and change rapidly. Our ability to assess the effects on gonadal function has been greatly enhanced by the development of new markers of the number of small follicles in women (i.e., anti Mü llerian hormone; Anderson et al 2006) and endocrine markers of spermatogenesis in men (i.e., inhibin B; van Beek et al 2007). It is hoped that the demonstration that ovarian tissue cryopreservation can be successful and of increased success rates with oocyte cryopreservation/vitrification (Gook & Edgar 2007) will encourage the collaborations needed between oncologists and reproductive specialists to investigate and develop these techniques further.…”
mentioning
confidence: 99%